2017
DOI: 10.1002/humu.23212
|View full text |Cite
|
Sign up to set email alerts
|

Single-base substitutions in theCHMpromoter as a cause of choroideremia

Abstract: 45Although over 150 unique mutations affecting the coding sequence of CHM have been identified 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 peripheral vision (Karna, 1986;Roberts et al., 2002). 76To date, CHM has only been linked to mutations within the CHM gene, coding for REP-1 77 (Cremers et al., 1990). The protein serves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Recent studies have highlighted that molecular diagnostic yield is increased when WGS is employed by comparison with other methods [51]. It is expected that for many of the currently unresolved cases, pathogenic variants may be present in deep-intronic, promoter, enhancer regions or in genes that are not yet associated with an IRD [73,74]. Recent studies such as that in STGD1, highlighting the relative prevalence of deep intronic mutations in the ABCA4 gene, attest to the need for more extensive sequence analysis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted that molecular diagnostic yield is increased when WGS is employed by comparison with other methods [51]. It is expected that for many of the currently unresolved cases, pathogenic variants may be present in deep-intronic, promoter, enhancer regions or in genes that are not yet associated with an IRD [73,74]. Recent studies such as that in STGD1, highlighting the relative prevalence of deep intronic mutations in the ABCA4 gene, attest to the need for more extensive sequence analysis [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CNVs and splice variants as a source of as yet ‘unresolved’ pathogenic IRD mutations, variants in regulatory sequences, such as, promoter sequences or miRNAs, and their associated target sites, may also be implicated in some forms of IRD. Indeed a mutation in the seed region of microRNA-204 has been found to segregate in a family with autosomal dominantly inherited retinal dystrophy and bilateral coloboma ( 44 ), a 5’UTR sequence in the NMNAT1 gene has been implicated in a form of LCA ( 45 ) and recently a single base mutation in the promoter region of the CHM gene has been implicated as causative of choroideremia ( 46 ), all highlighting the potential role of regulatory mutations in some forms of IRD. The implementation of more extensive NGS strategies in the future will aid in characterising such IRD regulatory mutations.…”
Section: Deciphering the Genetic Pathogenesis Of Unresolved Irdsmentioning
confidence: 99%
“…8 The ubiquitous expression profile of REP-1 and the essential role of Rab prenylation could suggest that CHM may also result in systemic abnormalities. 9,10 While certain Rabs have indeed been associated with syndromic diseases such as Griscelli syndrome type 2 (Rab27) and Charcot-Marie-Tooth disease type 2B (Rab7), 11,12 CHM has been viewed as a retinal disease, with no significant nonocular symptoms reported in males or carrier females. Previous work has demonstrated that a loss of REP-1 in fibroblasts and monocytes affected intracellular transport, increased pH levels in lysosomes, impaired proteolytic degradation, and altered secretion of cytokines, but these effects did not appear to translate to wider systemic effects.…”
mentioning
confidence: 99%